Hereditary pigmented paravenous chorioretinal atrophy - (:unkn) unknown (AEOLUS PRESS, 1998)
Pigmented paravenous chorioretinal atrophy (PPCRA) is a rare disorder which is diagnosed primarily because of the typical fundoscopic appearance of retinal pigment epithelial (RPE) atrophy and clumping in a paravenous distribution. A mildly affected and asymptomatic 54-year-old mother and her mildly affected daughter and severely affected son presented with pigmented paravenous chorioretinal atrophy. The severely affected (proband) 28-year-old man manifested the characteristic paravenous chorioretinal atrophy with pigment clusters in both eyes with macular involvement. Besides the characteristic fundus picture, he also had chronic angle closure glaucoma. His 23-year-old sister presented with unilateral involvement. Her right eye showed focal perivenular retinal pigment epithelial hyperplasia at the 2 o'clock position and dilated, tortuous retinal veins, while her left eye had only dilated and tortuous retinal veins. Both patients were hyperopic. Their mother had an area of chorioretinal atrophy in one eye near a retinal vein. The scotopic ERG responses were markedly abnormal in the male patient, while his sister had a mild decrease in amplitude of both a and b waves in both eyes. One of the children of an unaffected family member was found to have dilated and tortuous retinal veins and hyperopia (III-12). To our knowledge, this is the fourth report of familial occurrence of pigmented paravenous chorioretinal atrophy. The present pedigree is compatible with X-linked recessive or dominant inheritance.
Keywords: pigmented paravenous chorioretinal atrophy; chronic angle closure glaucoma; RETINOCHOROIDAL ATROPHY